2010
DOI: 10.1179/146532810x12858955921357
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia in vitamin D-dependent rickets type II responding to 1α-hydroxycholecalciferol

Abstract: A 4-year-old boy presented with rickets, alopecia and macrocephaly along with elevated serum levels of 1,25(OH)₂D₃ which was diagnostic of vitamin D-dependent rickets type II. The rickets responded to conventional doses of 1α-hydroxycholecalciferol together with oral calcium supplement and there was also improvement in the alopecia. In patients with vitamin D-dependent rickets type II with alopecia, although rickets improves with treatment, improvement in alopecia has not been reported before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…6 There is one previous case report of alopecia in VDDR II responding to 1,25(OH)2 vitamin D3. 2 Authors also found a similar improvement in alopecia. There is a report of two patients with presentation of only alopecia in the absence of rachitic changes, which might be explained by differences in sensitivity to 1,25(OH)2D3 of bone formation and hair growth.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…6 There is one previous case report of alopecia in VDDR II responding to 1,25(OH)2 vitamin D3. 2 Authors also found a similar improvement in alopecia. There is a report of two patients with presentation of only alopecia in the absence of rachitic changes, which might be explained by differences in sensitivity to 1,25(OH)2D3 of bone formation and hair growth.…”
Section: Discussionmentioning
confidence: 67%
“…Our patient had alopecia with severe deformities, aiding the diagnosis, VDDRII is an extremely rare disorder caused by target organ resistance to 1,25(OH)2 vitamin D, the biologically active form of vitamin D. There are a few isolated case reports from India earlier but the exact prevalence of the disease is not yet known. 2,3 It is diagnosed through the finding of normal or elevated circulating levels of 1,25(OH)2 vitamin D, which differentiate it from vitamin D-dependent rickets type I (VDDR I). The latter is caused by defective1-α hydroxylation of 25(OH) vitamin D in the kidneys, resulting in low serum levels of 1,25(OH) vitamin D3.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, alopecia associated with vitamin D deficiency seems mostly to be a feature of vitamin D deficiency associated with type II rickets. 103 Vitamin C deficiency has also rarely been reported to cause diffuse alopecia, with response to supplementation reported in a single case. 104 However, severe vitamin C deficiency is not associated with IBD specifically.…”
Section: Other Nutritional Deficienciesmentioning
confidence: 97%
“…18,23 The mechanism by which the VDR regulates hair growth is still poorly elucidated. 4,17,20,21,24 However, alopecia was related to the type of mutation in VDR gene. 11,13 Screening is crucial.…”
Section: Alopecia As a Sign Of Hypocalcemia Vitamin D-dependent Ricmentioning
confidence: 99%
“…Treatment of HVDDR2 is essential before reaching 3 years of age to avoid complications. 4,24 It consists of high doses of calcitriol and calcium supplementation. 13,16,18,19 Slight or no improvement of alopecia is usually reported.…”
Section: Alopecia As a Sign Of Hypocalcemia Vitamin D-dependent Ricmentioning
confidence: 99%